Digitalization Progress of Depositories in India : Evidences and Outcome - Gupta, Lovleen; Mohapatra, Amiya Kumar; Goel, Tripti (Indian Journal of Research in Capital Markets, 2021)
A depository is an institution that assists and enables storing and trading of securities in dematerialized form. India is a country with a multi-depository system, constituted of two main depositories, that is, National Securities Depository Ltd. (NSDL) and Central Depository Services (India) Ltd. (CDSL). The development of technology has paved the way for the innovative development of the depository system in India. The present study focused on discussing and analyzing the dual aspects of the digitalization progress of Indian depositories since its incorporation. First of all, in terms of e-services introduced by the depositories and then in terms of growth of demat securities, demat value of traded securities, companies live on any depository, DPs live, the number of DP locations, and number of investor accounts with DPs. The results showed that the adoption of the latest technology at nascent stages helped depositories achieve phenomenal growth rates over the years. The presence of a multi-depository system and many depository participants increased the accessibility for the investors and healthy competition in the capital market. Various digital services provided by the depositories have fastened the capital market development and client satisfaction. Improvization, innovation, and effective implementation of regulations have led to the remarkable progress of digitalization of depositories in India.